Application of Bioplastic with Corn Cob Cellulose and Chitosan as Active Packaging for Pempek Products - Pratiwi, Nurma; Putri, Pridata Gina; Fahrulsyah; Agassi, Taufik Nugraha; Joen, Deary Amethy Zahrotinufus (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Pempek is a fish-based food product that is highly susceptible to spoilage due to its elevated water and protein content, which fosters microbial growth. The reliance on conventional plastic packaging, such as polypropylene, raises environmental concerns, underscoring the need for alternative, more eco-friendly packaging solutions that enhance product safety. This study aimed to utilize bioplastics derived from corn cob cellulose and chitosan as active packaging to mitigate the deterioration of pempek during storage. The research involved extracting corn cob cellulose via the organosolv method, fabricating bioplastics via solution casting, packaging the pempek, and assessing Total Plate Count (TPC) and pH levels over 4 days of storage at room temperature. The findings revealed that the active bioplastic significantly inhibited microbial growth. The TPC of pempek packaged in bioplastic was 1–2 logs lower than that of the control on days 2-4. Additionally, the pH of the bioplastic-preserved pempek declined from 6.75 to 5.46, whereas the control increased from 7.77 to 8.17, indicating microbial spoilage. These results suggest that bioplastic incorporating corn cob cellulose and chitosan effectively slows deterioration, enhances microbiological safety, and presents a viable, environmentally friendly packaging alternative for food products. Contribution to Sustainable Development Goals (SDGs):SDG 12 – Responsible Consumption and ProductionSDG 13 – Climate ActionSDG 14 – Life Below WaterSDG 15 – Life on Land